Preliminary Clinical Study of a LenSx Femtosecond Laser-Assisted Limbal Relaxing Incision for the Correction of High Myopia with Low to Moderate Astigmatism in Posterior Implantable Collamer Lens Implantation - Miaomiao Zhu; Jilin Tan; Zhongxiu Zhao; Xialu Liu; Yanli Peng (Journal of Ophthalmology)
Purpose. To evaluate the safety, efficacy, and predictability of implantable collamer lens (ICL) implantation combined with a LenSx femtosecond laser-assisted limbal relaxing incision (LRI) for the correction of corneal astigmatism. Methods. This prospective study enrolled 64 eyes (54 patients) with high myopia with low to moderate regular corneal astigmatism. They were divided into an ICL group with ICL implantation (18 patients, 20 eyes), a TICL group with toric ICL implantation (17 patients, 23 eyes), and a LenSx + ICL group with a LenSx femtosecond laser-assisted LRI and an ICL implantation (19 patients, 21 eyes). Visual acuity, astigmatism correction ability, and visual quality were measured before and 1, 3, and 6 months after surgery. Results. The postoperative visual acuity of the 3 groups was higher than the preoperative visual acuity (P<0.01), and the improvements in the LenSx + ICL group and the TICL group were greater than those in the ICL group (P<0.01). The LenSx + ICL and TICL groups had less residual astigmatism and a higher astigmatism correction index (CI) than the ICL group (P<0.01). There was no significant difference among the three groups in total high-order aberrations (HOAs) before and after surgery (P>0.05). Conclusion. LenSx femtosecond laser-assisted LRI can effectively correct low to moderate corneal astigmatism during ICL implantation surgery. It can achieve similar clinical effects in the short term compared with TICL implantation.